Comparative appraisal of FT MIR spectra of ghee (heat clarified milk fat) with that of the mutton tallow and vegetable fat - Mehta, Bhavbhuti M. (Indian Journal of Dairy Science, 2018)
The FT MIR reflectance spectroscopy was examined in spectral pattern of ghee, mutton tallow and vegetable fat. To obtain MIR spectra, the samples were scanned in reflectance mode in the MIR region (4000–650 cm−1). The absorbance values of ghee as well as the fats at 3.5 µm and 5.7 μm were recoded from their respective spectrogram. The differences between spectra of ghee and that of the mutton tallow as well as vegetable fat to varying extent were noticed at 3100 cm─1 and 1750 cm─1.